Making a movie or making a difference? What is the impact of critical movies and documentaries targeting corporate wrongdoing? - Seth, Rohan Rapahel (2010)
Using the case of ‘Wal-Mart: The High Cost of Low Price’, I shall attempt to understand what the influence of critical movies has been on corporate strategies. In order to build a theoretical framework on which to base the research I will be exploring theories that examine the role played by non-market factors such as the media, stakeholder theory etc. I will try to understand if the movie and the debate around it resulted in any kind of change within the corporation and whether the changes, if any, have been just a temporary response or more of a permanent change. An attempt will also be made to examine the political orientations of the media and whether this has an affect on the debate. The research showed that the media did influence Wal-Mart both in the short run and in the long run.